Stephen Reckert, Beyond Chrysanthemums: Perspectives on poetry east and west - Mariana Masera (Medievalia)
Stephen Reckert, Beyond Chrysanthemums: Perspectives on poetry east and west, Oxford: Clarendon Press: 1993, 271 pp.